Qingfeiyin Decoction Inhibits H1N1 Virus Infection via Modulation of Gut Microbiota and Inflammatory Pathways in a Murine Model - Li, Xianping; Wang, Mingzhe; Liu, Chang; Xiao, Yuchun; Li, Mengde; Ban, Chengjun; Huang, Yuanming; Cheng, Miao; Song, Liqiong; Liu, Guoxing; Lu, Shan; Wang, Chengxiang; et al. (Frontiers in Pharmacology, 2022)
Influenza virus-caused lung infection and its pandemic outbreaks are a persistent public health challenge. H1N1 subtype is the most common type of influenza infection observed in humans. Maxingshigantang decoction, a classic formula of Chinese herbal medicine, has been used for the prevention and treatment influenza for thousands of years. Qingfeiyin decoction, based on maxingshigantang, has been used in the clinic for decades. To explore the underlying mechanisms, according to the TCM theory ‘the lung and the large intestine are interior-exterior’, the composition of gut microbiota was determined using 16S rRNA and transcriptome of colon determined by RNA sequencing. The results showed that Qingfeiyin decoction decreased the viral loading, alleviated the lung injury, increased the survival rate, partly restored the shortening of the colon caused by the H1N1 virus, and down-regulated inflammatory pathways including MAPK, TNFα, and JAK-STAT signaling pathways. Qingfeiyin decoction increased the relative abundance of the genera of coprococcu, ruminococcus, lactobacillus, and prevotella, and prevented the decrease in the level of genera of escherichia, parabacteroides, butyricimonas, and anacrotruncus caused by H1N1 virus. These results help better understand the mechanisms for Qingfeiyin decoction’s protective effect against influenza virus infection.